Enhanced design of cascade control systems for unstable processes with time delay. (September 2016) - Dasari, Purushottama Rao; Alladi, Lavanya; Seshagiri Rao, A.; Yoo, ChangKyoo
Highlights: Simple IMC based controller is designed based on H2 minimization. Provides significant disturbance rejection performances. Provides significant improvement when compared to the recently reported methods in the literature. Able to provide good stable closed loop response even when there are large amount of perturbations in the process parameters. Quantitative comparison has been carried out by considering integral absolute error (IAE) and total variation (TV). Abstract: In this paper, optimal H2 internal model controller (IMC) is designed for control of unstable cascade processes with time delays. The proposed control structure consists of two controllers in which inner loop controller (secondary controller) is designed using IMC principles. The primary controller (master controller) is designed as a proportional-integral-derivative (PID) in series with a lead-lag filter based on IMC scheme using optimal H2 minimisation. Selection of tuning parameter is important in any IMC based design and in the present work, maximum sensitivity is used for systematic selection of the primary loop tuning parameter. Simulation studies have been carried out on various unstable cascade processes. The present method provides significant improvement when compared to the recently reported methods in the literature particularly for disturbance rejection. The present method also provides robust closed loop performances for large uncertainties in the process parameters. Quantitative comparison has been carried out by considering integral of absolute error (IAE) and total variation (TV) as performance indices.